SYNTHESIS AND CHARACTERIZATION OF 3-ARYL-5H,13AH-QUINOLINO(3,2-F) (1,2,4)TRIAZOLO(4,3-B)(1,2-DIAZA-4-SULPHO)AZEPINES: IN VITRO ANTIFUNGAL AND ANTIBACTERIAL ACTIVITY - Hemant Panwar; Shishupal Singh (Universitas Gadjah Mada, 2011)
3-Aryl-5H,13aH-quinolino(3,2-f)(1,2,4)triazolo(4,3-b)(1,2-diaza-4-sulpho)azepines [2a-i] have been prepared by the cyclisation of 5-aryl-4-amino-3-mercapto-1,2,4-triazole by reaction with 2-chloro-3-formylquinoline in catalytic presence of p-toluene sulphonic acid. All the synthesized compounds have been characterized by elemental and spectral (IR, 1H- NMR and Mass) analysis. Furthermore, all compounds were evaluated for their antibacterial and antifungal activities against selected panel of pathogenic strains. Ampicillin trihydrate and fluconazole were used as standard drugs for antibacterial and antifungal activity, respectively. 3-(2-Chloro)phenyl-5H,13aH-quinolino(3,2-f)(1,2,4)triazolo(4,3-b)(1,2-diaza-4-sulpho)azepine [2h] was found, one of the most potent with lesser toxicity among the all prepared thiazepine derivatives.